Testing coherence in narrative film - Aikaterini, V (2016)
This thesis aims to explore how narrative films that are marked by crucial obscurities and explanatory gaps in their development manage to become coherent. More specifically, the thesis is interested in examining how these obscurities and explanatory gaps can be understood as meaningful aspects of the films' organisation. Since the function of coherence in film has rarely been examined directly, the thesis first attempts to illuminate it by drawing on the work of two aestheticians who have examined it more systematically. Thus, the first part of the thesis discusses the work of Victor F. Perkins and George Wilson, while attempting to explore aspects of the work of these two aestheticians through the analysis of specific films. The writings of Perkins and Wilson provide a good starting point for the thesis because they raise crucial questions regarding the ways through which narrative films manage to deal with significant tensions in their organisation and intelligibility. The main body of the thesis (the second part of the thesis) then examines four narrative films, each of which is marked by a significant aspect of apparent incoherence. In each case, the thesis attempts to show that this aspect of apparent incoherence – rather than merely obstructing the film’s intelligibility – essentially contributes to the creation of the film’s idiosyncratic internal logic. In order to understand how this becomes possible, the thesis pays close attention to the ways in which the various components of each examined film relate to each other, observing and analysing the aesthetic strategies which enable each examined film ultimately to come together.